Isytiqoq Perspektif Aliran Basrah dan Kufah - Mas Tajuddin Ahmad (Indonesian Journal of Arabic Studies, 2020)
in linguistics, there are studies that focus on making sentences and part of them. Commonly, people call it syntax. No exception in the discipline of Arabic Linguistics, in that discipline there is also a study of syntax, it called Nahwu or Ilmu An Nahwi. The problems in the study of Nahu Science do not stop only at the level of sentences and parts thereof. However, very long before that, there were some schools (madrasah) of critical thingking about the Nahu Science itself. Among the famous schools are Basrah and Kufa. Next will be explained the perspective of the two schools (madrasas) about the Origin of Words Theory (Isytiqoq). The purpose of this study is in order that the reader can find out the concept of isytiqoq according to each schools. This research uses a type of qualitative research methods using various sources of literature related to research. Through this research, we will get results about the theory of isytiqoq Basrah which are oriented towards nouns and kufa based on verbs.Â